Friends or parents? Thomas (Journal of Parents and Teachers, 2014)
Thomas´s story, a capricious and impolite child who has been consented by his father from an early age, serves as a starting point for a didactic reflection.
Keywords: Family; parents; friends; education; consent; happiness; problems.